Auditor-provided non-audit services and perceived audit quality: Evidence from the cost of equity and debt capital - Christian Friedrich; Reiner Quick; Florian Schmidt (International Journal of Auditing, 2022)
There is an ongoing debate among regulators and researchers about concerns that the provision of non-audit services (NAS) to audit clients may impair audit quality by reduced independence. In this context, there can be different perspectives on audit quality. Given recent regulatory changes in the European Union (EU) aimed to improve investor confidence in audited financial statements, it is critical to understand the association of NAS and audit quality perceptions by investors before and after the regulation. We investigate whether NAS affect shareholder and lender perceptions of audit quality, measured by the cost of debt and equity capital. For a sample of German firms, we find significant positive associations of NAS with both cost of debt and cost of equity. Other assurance and consultancy services drive this effect. We do not find this effect in the pre-regulation period, but in the transition period when the regulation was passed but NAS restriction did not yet apply. In the post-regulation period, it only persists for lenders. Thus, the EU regulation may have increased (or inadequately created) independence concerns for shareholders and lenders and curbed these concerns for shareholders only.
Keywords: 650; auditor independence; cost of debt capital; cost of equity capital; financial reporting credibility; non-audit services; perceived audit quality